Protecting and accessing data from the survey of earned doctorates : a workshop summary - Plewes, Thomas J. (National Academies Press, 2010)
"The Survey of Earned Doctorates (SED) collects data on the number and characteristics of individuals receiving research doctoral degrees from all accredited U.S. institutions. The results of this annual survey are used to assess characteristics and trends in doctorate education and degrees. This information is vital for education and labor force planners and researchers in the federal government and in academia. To protect the confidentiality of data, new and more stringent procedures were implemented for the 2006 SED data released in 2007. These procedures suppressed many previously published data elements. The organizations and institutions that had previously relied on these data to assess progress in measure of achievement and equality suddenly found themselves without a yardstick with which to measure progress. Several initiatives were taken to address these concerns, including the workshop summarized in this volume. The goal of the workshop was to address the appropriateness of the decisions that SRS made and to help the agency and data users consider future actions that might permit release of useful data while protecting the confidentiality of the survey responses."--Website description.